The incidence chromatic number of some graph - Liu Xikui; Li Yan (International Journal of Mathematics and Mathematical Sciences)
The concept of the incidence chromatic number of a graph was introduced by Brualdi and Massey (1993). They conjectured that every graph G can be incidence colored with Δ(G)+2 colors. In this paper, we calculate the incidence chromatic numbers of the complete k-partite graphs and give the incidence chromatic number of three infinite families of graphs.